Story telling, career assessment and career counselling: A higher education case study - McMahon, Mary; Watson, Mark; Hoelson, Christopher; Chetty, Candice (South African Journal of Higher Education, 2016)
Narrative and storied approaches to career counselling have become more prominent in recent decades. This paper presents a case study of a Xhosa-speaking woman who presented for career counselling in a South African higher education career service. It describes how career assessment can be incorporated into a story telling approach to career counselling in order to facilitate a holistic exploration of an individual client’s career situation. The My System of Career Influences (MSCI) (Adult) reflection process and a career values card sort were utilized within a career counselling intervention based on a story telling approach to career counselling. Suggestions are offered for career counsellors and also counsellor educators.